33‐2: Invited Paper: Lifetime Improvement of Thermally Activated Delayed Fluorescent Organic Light‐Emitting Diodes. Issue 1 (29th May 2019) - Lee, Ho Jung; Lee, Kyung Hyung; Lee, Jun Yeob; Hong, Wan Pyo; Song, Ok-Keun
Abstract : The external quantum efficiency of thermally activated delayed fluorescent organic light‐emitting diodes has been improved to the same level of phosphorescent organic light‐emitting diodes. However, the lifetime of the thermally activated delayed fluorescent organic light‐emitting diodes is not comparable to that of the phosphorescent organic light‐emitting diodes. Therefore, the lifetime of the thermally activated delayed fluorescent devices needs to be extended. In this work, the lifetime extending strategy of thermally activated delayed fluorescent organic light‐emitting diodes from molecular design approach is proposed. The molecules with a chemical bond stabilizing molecular design and high reversed intersystem crossing rate were effective to extend the lifetime of the thermally activated delayed fluorescent organic light‐emitting diodes.